A dispenser–reactor apparatus applied for in situ XAS monitoring of Pt nanoparticle formation - Boita, Jocenir (2015)
In situ time-resolved X-ray absorption spectroscopy (XAS) measurements collected at the Pt L3-edge during the synthesis of Pt nanoparticles (NPs) in aqueous solution are reported. A specially designed dispenser–reactor apparatus allowed for monitoring changes in the XAS spectra from the earliest moments of Pt ions in solution until the formation of metallic nanoparticles with a mean diameter of 4.9 1.1 nm. By monitoring the changes in the local chemical environment of the Pt atoms in real time, it was possible to observe that the NPs formation kinetics involved two stages: a reduction-nucleation burst followed by a slow growth and stabilization of NPs. Subsequently, the synthesized Pt NPs were supported on activated carbon and characterized by synchrotron-radiation-excited X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and extended X-ray absorption fine structure (EXAFS). The supported Pt NPs remained in the metallic chemical state and with a reduced size, presenting slight lattice parameter contraction in comparison with the bulk Pt values.